Protective Effect of Lemongrass and Cinnamon Essential Oil Lotion Against Aedes aegypti - Indah Arlitasari, Silvia; Porusia, Mitoriana (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
Dengue hemorrhagic fever (DHF) is still a health problem and threat in several regions of Indonesia. Using mosquito repellent can prevent the incidence of dengue fever. In the industrial world, products such as mosquito repellent lotion are released. Lotions circulating in the community contain DEET. Bug sprays with chemicals can be replaced with natural bug sprays made from things like the essential oils Cymbopogon nardus (C.n.) and Cinnamomum burmannii (C.b.), which contain chemicals that kill mosquitoes. This study employs an experimental laboratory approach, utilizing a post-test-only group design. The goal of this study was to find out how well mosquito repellent lotion made with Cymbopogon nardus (C.n) essential oil and Cinnamomum burmannii (C.b) essential oil worked at keeping people safe. Aedes aegypti mosquito samples totaled 1200 mosquitoes. Each treatment was repeated six times (50 mosquitoes). B2P2VRP Salatiga research location. A repellent test is used to collect data. Data processing is carried out with the Anova statistical test. The Anova statistical test was used to process the data. On average, lotions at 400 ppm C.N. provided the most protection at the 1st hour (82.16%) and the 6th hour (50.12%). The conclusion of this study was that, although it did not reach the effective value (<90%), with the addition of concentration, it is possible to increase repulsiveness. So, more research can be done on the effectiveness of Cymbopogon nardus essential oil and Cinnamomum burmannii essential oil by mixing them in lotions in different ways.